Effectiveness of Project Based Learning on Outcome Based Education-A Case Study - Prasanna Kumar, M. K.; Agrawal, Soniya; Bhat, Hemachandra (Journal of Engineering Education Transformations, 2016)
The objective of this paper is to present the effectiveness of Project Based Learning incorporating the development of student's soft skills like communication and team work as well as technical or professional competences such as deep thinking and learning. A case study in the form of one month value added course on Project based learning using Unified Technology Learning Platform (UTLP) for Electrical cluster students is implemented. The learning outcome of the student is evaluated at regular intervals during the course. These outcomes are driven by institution's vision of the knowledge and skills that students need to acquire in order to be independent and a life long learner. This paper shows how project based learning can be used to facilitate for the production of qualified and well prepared professionals. This paper also presents an approach for the project assessment used to make the learning outcomes effectively.